Oral Hygiene Product for Tooth Whitening Based on the Natural Product Curcumin - Allal Nawel; Guendouz Souhila; Baba Ahmed Nawel; Oudghiri Fouad (Biology and Life Sciences Forum)
Introduction: In everyday life, many people smoke, eat colored foods, and drink coffee, tea, and other beverages. The use of herbal products containing natural ingredients is better accepted by the public because of their safety. The aim of the present study was to develop two formulations of curcumin-based gels and investigate their anti-dyschromic qualities in teeth. Materials and Methods: This is an in vitro therapeutic clinical trial. A series of experiments was carried out on extracted teeth (n = 30). Samples were randomly divided into five subgroups. Readings were taken initially (T1), and then after immersion in a blackening process (T2). The brightening agent was applied for 5 min, three times a day. After 30 days of applications, new measurements were taken using a Vita Classical shade guide. Results: The curcumin and xanthan gum hydrogel that was used topically demonstrated superior efficacy in reducing dental dyschromia. These promising results suggest that this formulation could be an attractive option for the treatment of dental dyschromia. Conclusions: Curcumin-based gel presents itself as a promising candidate for the prevention and/or treatment of dental dyschromia. In addition, it has an excellent safety profile.